Shooting Victoria madness, mayhem, and the rebirth of the British monarchy - Murphy, Paul Thomas 1957- (Pegasus Books, 2012)
From a hunchbacked dwarf to a paranoid poet assassin, a history of Victorian England as seen through the numerous assassination attempts on Queen Victoria
Includes bibliographical references (p. 641-658) and index
Keywords: Victoria / Queen of Great Britain / 1819-1901 / Assassination attempts; Viktoria -- Großbritannien, Königin -- 1819-1901; Geschichte 1800-1900; Geschichte; Politik; Attentat; Great Britain / History / Victoria, 1837-1901; Great Britain / Politics and government / 1837-1901; Great Britain / Social conditions / 19th century; Großbritannien